2009
DOI: 10.1002/ejoc.200900043
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Zn‐Brook Rearrangement/Ene‐Allene Carbocyclization

Abstract: The addition of metalated alkynes to acylsilanes leads to the corresponding α‐propargylsilanol derivatives. On addition of ZnBr2, Zn‐promoted Brook rearrangements take place to produce the propargyl/allenylzinc bromides, which undergo cyclization to give functionalized carbocycles as single diastereoisomers. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Similarly, the lithium salt of α-silylpropargylic alcohol 1 Li , generated by the addition of lithium acetylide to acylsilane, does not lead experimentally to the Brook rearrangement product 2 Li (or 3 Li after metallotropic equilibrium, Scheme , Path B) since none of the adducts 4 and/or 5 are obtained after hydrolysis. Only when an excess of the starting alkyne is used (2 equiv of an alkyne for 1 equiv of alkynyl lithium), the reaction can be shifted to the products 4 and/or 5 through protonation of 2 Li or 3 Li by the acidic acetylenic hydrogen atom (E-X = R 2 CC-H, Scheme , Path B) …”
Section: Results and Discussionmentioning
confidence: 99%
“…Similarly, the lithium salt of α-silylpropargylic alcohol 1 Li , generated by the addition of lithium acetylide to acylsilane, does not lead experimentally to the Brook rearrangement product 2 Li (or 3 Li after metallotropic equilibrium, Scheme , Path B) since none of the adducts 4 and/or 5 are obtained after hydrolysis. Only when an excess of the starting alkyne is used (2 equiv of an alkyne for 1 equiv of alkynyl lithium), the reaction can be shifted to the products 4 and/or 5 through protonation of 2 Li or 3 Li by the acidic acetylenic hydrogen atom (E-X = R 2 CC-H, Scheme , Path B) …”
Section: Results and Discussionmentioning
confidence: 99%
“…This initial approach was further improved when it was found that a tandem Zn-promoted Brook rearrangement−carbocyclization reaction also leads to the cyclic product in similar yields and diastereoselectivities (Scheme ) . However, to have an enantio- and diastereoselective Zn−ene−allene carbocyclization reaction, we have to address the challenging in situ preparation and cyclization of enantiomerically enriched allenylzinc species.…”
mentioning
confidence: 99%
“…On the other hand, we have recently reported that a Meerwein–Ponndorf–Verley-type reduction of alkynoylsilanes 4 via a hydride transfer from a chiral lithium amide (Scheme , Nu = H – ) affords siloxyallenes 6 via a Brook rearrangement in the resulting α-silyl alkoxide 5 followed by stereoselective protonation across the triple bond . These findings led us to consider the possibility of employing a cyanide ion in place of a hydride as a nucleophile, which would afford allene derivatives bearing cyano and siloxy functions at the same carbon atom …”
Section: Introductionmentioning
confidence: 99%